2017
DOI: 10.1038/s41598-017-11695-y
|View full text |Cite
|
Sign up to set email alerts
|

A brain-targeting lipidated peptide for neutralizing RNA-mediated toxicity in Polyglutamine Diseases

Abstract: Polyglutamine (PolyQ) diseases are progressive neurodegenerative disorders caused by both protein- and RNA-mediated toxicities. We previously showed that a peptidyl inhibitor, P3, which binds directly to expanded CAG RNA can inhibit RNA-induced nucleolar stress and suppress RNA-induced neurotoxicity. Here we report a N-acetylated and C-amidated derivative of P3, P3V8, that showed a more than 20-fold increase in its affinity for expanded CAG RNA. The P3V8 peptide also more potently alleviated expanded RNA-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…As MDA and LDH are the most commonly used markers of oxidative damage to lipids and cytotoxicity, respectively, we investigated whether Gas affects these biochemical indicators 17,18 . The MDA and LDH levels were significantly higher in the model group than in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As MDA and LDH are the most commonly used markers of oxidative damage to lipids and cytotoxicity, respectively, we investigated whether Gas affects these biochemical indicators 17,18 . The MDA and LDH levels were significantly higher in the model group than in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…As MDA and LDH are the most commonly used markers of oxidative damage to lipids and cytotoxicity, respectively, we investigated whether Gas affects these biochemical indicators. 17,18 The MDA and LDH levels were significantly higher in the model group than in the control group. The MDA levels in the presence of Gas (50-800 µg/ mL) also showed a dose-dependent reduction with a maximal decrease at 800 µg/mL, and the LDH levels showed significant differences in the 200 to 800 μg/mL Gas groups ( Figure 1C, D).…”
Section: Gas Inhibited the Hcy-induced Increases In Ros Levels Mdamentioning
confidence: 93%
“…In this study, we made acetylated and non-acetylated versions of our analogues. Although N-terminal acetylation can alter peptide function [ 46 ], in the case of relaxin-3, the difference in binding and potency of acetylated and non-acetylated analogues were not markedly different. No obvious differences in secondary structure where noted when the N-terminus was acetylated; however, to avoid unfavourable electrostatic interactions between a positively charged N-terminus and the helix dipole, acetylation of these shorter analogues makes sense and is likely to also provide better in vivo stability.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of lipidation strategies have been reviewed to convert peptides to drug leads by altering the physiochemical properties of the peptides (Zhang and Bulaj, 2012). Lipidated peptides have increased plasma stability and prolonged elimination time due to serum albumin binding (Zhang et al, 2017). As part of a potential gene delivery strategy, it was observed that a fluorescently-labelled DNA/fatty acid complex could still be seen in circulation 48 h post injection, indicating a long half-life of the lipidated complex cargo .…”
Section: Lipidationmentioning
confidence: 99%
“…Myristoylation has also been shown to prolong peptide-siRNA complex stability in serum, allowing more time for cellular uptake of the siRNA complex (Youn et al, 2014). For peptides, palmitoylation of the 13-residue P3V8, a peptidylic inhibitor, has been shown to improve peptide stability in rat plasma and brain homogenate without diminishing P3V8's ability to inhibit retinal degeneration in a Drosophila model (Zhang et al, 2017). Cationisation using polyamines have also been shown to improve CNS bioavailability of proteins and peptides (Poduslo and Curran, 1996;Zhang et al, 2009a) and a combination of lipidation and cationisation of neuropeptides (galanin, neurotensin and neuropeptide W) was found to increase plasma stability and increase in vivo efficacy (Bulaj et al, 2008;Green et al, 2010;Green et al, 2011).…”
Section: Lipidationmentioning
confidence: 99%